Short-term resilience-oriented enhancement in smart multiple residential energy system using local electrical storage system, demand side management and mobile generators - Kashanizadeh, Babak; Shourkaei, Hosein Mohammadnezhad; Fotuhi-Firuzabad, Mahmud (Journal of energy storage, 2022)
Recently, many investigations have been studied on the effects of the uncommon extreme events like hurricanes in electrical distribution grids. These events leads to damage to distribution grid equipments, and they are cause widespread blackouts. This paper presents short-term resilience enhancement of the residential sections against hurricane at day-ahead. The lines outage in the electrical distribution grid is implemented as stochastic modeling by hurricane. The resilience enhancement is done in the multiple energy systems such as integrated gas, heat and electrical. The three-stage multi-objective functions optimization is proposed for resilience-oriented enhancement. The proposed strategy for resilience-oriented enhancement including installation of the mobile generators (MGs), implementation of the demand side management (DSM) strategy and local generation (LG) in each stage. In first stage optimization, minimizing the installation costs of the MGs is modeled subject to lines outage. The DSM strategy is modeled in second stage optimization as minimization of the electrical demand deviation than optimal demand level at day-ahead. Then, minimization of the 1) operation cost and 2) loss of power supply probability (LPSP) index are considered in third stage optimization. In addition to, installation of the MGs and DSM in first and second stages; LG by electrical storage systems (ESSs) in third stage optimization is taken into accounted. The effectiveness of the proposed strategies is confirmed on the IEEE 33-bus distribution grid as three case studies by numerical simulation. The obtained results for operation cost and LPSP index in first case are $1,098,833.4 and 0.11 kW, respectively. In second case, LPSP index is minimized by %52.2 than first case. Finally, operation cost and LPSP in third case and with participation of the ESS are reduced by %52.2 and %0.78 in comparison to second case, respectively. •A three-stage multi-objective optimization is proposed to enhancement of the resilience-oriented.•The preventive response strategy of the resilience-oriented terms is implemented at day-ahead.•The MGs installation, LG and DSM are considered as preventive response strategies.•The implementation of the DSM is independent of the electrical price in EC.•Minimization of the operation costs and LPSP are considered as multi-objective functions in third stage optimization.